2008
DOI: 10.1158/0008-5472.can-07-3036
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid CDDO-Methyl Ester Inhibits the Janus-Activated Kinase-1 (JAK1)→Signal Transducer and Activator of Transcription-3 (STAT3) Pathway by Direct Inhibition of JAK1 and STAT3

Abstract: The C-28 methyl ester of the oleane triterpenoid 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO-Me) induces apoptosis of human cancer cells by disrupting redox balance and is in clinical trials. CDDO-Me contains A,B-unsaturated carbonyl groups that form reversible adducts with thiol nucleophiles. The present studies show that CDDO-Me blocks interleukin-6 (IL-6)-induced and constitutive activation of the Janusactivated kinase 1 (JAK1) in cells. In support of a direct mechanism, CDDO-Me forms adducts with J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 42 publications
5
92
0
Order By: Relevance
“…16 The proposed mechanism underlying the anticancer effects of SOs is by the formation of Michael adducts between SOs and reactive nucleophiles, such as free thiols on target proteins. [17][18][19][20] The wide spectrum of SO effects is explained, in part, by their concentration-dependent induction of oxidative stress, which alters various redox-sensitive proteins and signaling networks. SOs show unique promise in the prevention and treatment of cancer, 16 and may also act synergistically with other anticancer agents to induce stress overload and/or stress sensitization.…”
mentioning
confidence: 99%
“…16 The proposed mechanism underlying the anticancer effects of SOs is by the formation of Michael adducts between SOs and reactive nucleophiles, such as free thiols on target proteins. [17][18][19][20] The wide spectrum of SO effects is explained, in part, by their concentration-dependent induction of oxidative stress, which alters various redox-sensitive proteins and signaling networks. SOs show unique promise in the prevention and treatment of cancer, 16 and may also act synergistically with other anticancer agents to induce stress overload and/or stress sensitization.…”
mentioning
confidence: 99%
“…CDDOMe was shown to inhibit IKKa kinase and subsequently IjBa protein phosphorylation and degradation, as well as NF-jB-dependent transactivation of the reporter gene [163]. Furthermore, both CDDO-Me and CDDO-Im could inhibit IKKb kinase by directly binding to Cys-179 and inhibiting the enzymatic activity of IKKb [164][165][166]. Sohn et al provided first evidence that OA have antiangiogenic effects on bovine aortic endothelial cells and in chick embryo chorioallantoic membrane assay [167].…”
Section: Oleanolic Acidmentioning
confidence: 99%
“…In many instances, it has been observed that these compounds bind to the active cysteine residue in the proteins [16]. The key proteins that have been reported to be modulated by oleanane triterpenoids are Keap 1 [193,194], IKK, IkBa and NF-jB [164,166], JAK1 and STAT3 [165,195,196], PTEN [197], AKT [14,198,199], mTOR [200], ROS [201], DR5 and CHOP [202], GSK3b [203], cFLIP and VEGF [204,205], mitochondrial membrane potential [206], and cell cycle arrest [198,207,208]. In another study where transgenic LSL-Kras(G12D/+); LSL-Trp53(R127H/+); Pdx-1-Cre (KPC) mouse model of pancreatic cancer were fed with diet containing CDDO-Me or CDDO-ethyl amide, the rexinoid LG100268 significantly increased the survival of mice by 3-4 weeks [209] and prevented lung cancer development when fed with these terpenoids for 8 weeks [15].…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%
“…Inhibition of STAT3 was shown to have anticancer activity in vitro and in animal models (30)(31)(32)(33)(34). Furthermore, direct inhibition of GP130 attenuates STAT3 activation and inhibits some cancer cells (9).…”
Section: Introductionmentioning
confidence: 99%